Translesion DNA polymerases in eukaryotes: what makes them tick? - Vaisman, Alexandra; Woodgate, Roger (Critical reviews in biochemistry and molecular biology, 2017)
Life as we know it, simply would not exist without DNA replication. All living organisms utilize a complex machinery to duplicate their genomes and the central role in this machinery belongs to replicative DNA polymerases, enzymes that are specifically designed to copy DNA. "Hassle-free" DNA duplication exists only in an ideal world, while in real life, it is constantly threatened by a myriad of diverse challenges. Among the most pressing obstacles that replicative polymerases often cannot overcome by themselves are lesions that distort the structure of DNA. Despite elaborate systems that cells utilize to cleanse their genomes of damaged DNA, repair is often incomplete. The persistence of DNA lesions obstructing the cellular replicases can have deleterious consequences. One of the mechanisms allowing cells to complete replication is " T rans l esion DNA S ynthesis (TLS)". TLS is intrinsically error-prone, but apparently, the potential downside of increased mutagenesis is a healthier outcome for the cell than incomplete replication. Although most of the currently identified eukaryotic DNA polymerases have been implicated in TLS, the best characterized are those belonging to the "Y-family" of DNA polymerases (pols η, ι, κ and Rev1), which are thought to play major roles in the TLS of persisting DNA lesions in coordination with the B-family polymerase, pol ζ. In this review, we summarize the unique features of these DNA polymerases by mainly focusing on their biochemical and structural characteristics, as well as potential protein-protein interactions with other critical factors affecting TLS regulation.